2016
DOI: 10.1097/icl.0000000000000210
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Ambient Temperature on the Human Tear Film

Abstract: Ambient temperature has a considerable effect on human tear film characteristics. Tear evaporation rate, tear LLT, tear stability, and OST were considerably affected by ambient temperature. Chronic exposure to low ambient temperature would likely result in symptoms of dry eye and ultimately ocular surface disorders.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
43
2
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(52 citation statements)
references
References 31 publications
(28 reference statements)
5
43
2
2
Order By: Relevance
“…Temperature did not affect STT1 readings in our sample group. A previous human study did, however, demonstrate a slight effect of environmental T on tear evaporation rate, tear break up time, lipid layer thickness, and ocular surface temperature 12 . Aside from the fact that we did not utilize the same metrics in our study group as those in this previous work, there is no clear explanation for this difference.…”
Section: Discussioncontrasting
confidence: 55%
“…Temperature did not affect STT1 readings in our sample group. A previous human study did, however, demonstrate a slight effect of environmental T on tear evaporation rate, tear break up time, lipid layer thickness, and ocular surface temperature 12 . Aside from the fact that we did not utilize the same metrics in our study group as those in this previous work, there is no clear explanation for this difference.…”
Section: Discussioncontrasting
confidence: 55%
“…A threefold increase in the TE rate was measured as ambient temperature increased to 25°C and from 25°C to 34°C . Low temperature has also an adverse effect by lower non‐invasive BUT (5 second less) and LL thickness (halved) at 5°C than at 25°C . Overall, both low RH and low/high temperature have detrimental effects on the PTF characteristics; this agrees with a more impaired performance of the meibum lipid film resulting in structural changes by reduced viscoelasticity or compositional changes …”
Section: Resultsmentioning
confidence: 58%
“…For instance, higher temperature lowers BF, in accord with stimulation of the thermo‐sensitive TRPM8 cold fibers in cornea that initiates reflex blinking by cooling . A threefold increase in the TE rate was measured as ambient temperature increased to 25°C and from 25°C to 34°C . Low temperature has also an adverse effect by lower non‐invasive BUT (5 second less) and LL thickness (halved) at 5°C than at 25°C .…”
Section: Resultsmentioning
confidence: 92%
“…In vitro and in vivo studies have shown that increasing the ambient temperature increases the tear evaporation rate, TBUT, lipid layer thickness, and ocular surface temperature [254,622]. High altitude exposure, with cold and dry air, leads to a decrease in TBUT and an increase in tear film osmolarity [148].…”
Section: Non-pathophysiological Factors Impacting the Tear Filmmentioning
confidence: 99%